Alkaloids isolated from Litsea grandis and Litsea lancifolia (Lauraceae) / Syazreen Nadia Sulaiman - Syazreen Nadia, Sulaiman (2012)
The phytochemical study on the leaves of Litsea grandis and on the barks of Litsea lancifolia involved extraction and separation of alkaloids by using dichloromethane as a solvent. The crude alkaloids obtained were subjected to extensive chromatographic techniques such as thin layer chromatography (TLC) and column chromatography (CC). The structural elucidations of the purified alkaloids were performed with the aid of spectroscopic methods notably 1D-NMR (1H, 13C, DEPT) and 2D-NMR(COSY, HMQC, HMBC, NOESY), UV, IR and LCMS-IT-TOF. The chemical study on the leaves of Litsea grandis gave three alkaloids; one aporphine (laurotetanine 69) and two benzylisoquinoline (reticuline 67 and N-methylisococlaurine 68). The investigation of the bark of Litsea lancifolia afforded eight alkaloids; one benzylisoquinoline; O-methylarmepavine 73; four aporphines; boldine 55, actinodaphnine 53, cassythicine 74 and norboldine 75; one morphinandienone type; pallidine 72; one new natural product compound; N-allyllaurolitsine 70; and one new bisbenzylisoquinoline; lancifoliaine 71.Three major alkaloids isolated from Litsea lancifolia; lancifoliaine 71, N-allyllaurolitsine 70, and reticuline 67 were tested for vasorelaxant activity. The results have shown that only N-allyllaurolitsine 70, showed a moderate vasorelaxant activity (85% relaxation at 1×10-4M), meanwhile lancifoliaine 71 and reticuline 67 did not show any significant vasorelaxant activity (30% relaxation at 1×10-4M) on isolated rat aorta.